2018
DOI: 10.1021/acs.jpcc.8b09360
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Synthesis Mechanism of Ag29 Nanoclusters

Abstract: The current understanding of the synthesis mechanisms of noble metal clusters is limited, in particular for Ag clusters. Here, we present a detailed investigation into the synthesis process of atomically monodisperse Ag29 clusters, prepared via reduction of AgNO3 in the presence of dithiolate ligands. Using optical spectroscopy, mass spectrometry, and X-ray spectroscopy, it was determined that the synthesis involves a rapid nucleation and growth to species with up to a few hundred Ag atoms. From these larger s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 67 publications
3
26
0
1
Order By: Relevance
“… 27–30 The X-ray single crystal structure of Ag 29 NCs was first revealed for Ag 29 (BDT) 12 (TPP) 4 NCs. 27 a A similar structure and composition were proposed for water soluble silver NCs prepared with bidentate DHLA ligands 29 by mass spectrometry data corresponding to an m / z value corresponding to the [Ag 29 (DHLA) 12 ] 3− composition, exhibiting absorption and photoluminescence spectra similar to those of Ag 29 (BDT) 12 (TPP) 4 NCs. 29 We have recently imparted optical activity to the NCs by using enantiomeric DHLAs and demonstrated mirror image CD and circular polarized luminescence (CPL) spectra.…”
Section: Introductionmentioning
confidence: 62%
“… 27–30 The X-ray single crystal structure of Ag 29 NCs was first revealed for Ag 29 (BDT) 12 (TPP) 4 NCs. 27 a A similar structure and composition were proposed for water soluble silver NCs prepared with bidentate DHLA ligands 29 by mass spectrometry data corresponding to an m / z value corresponding to the [Ag 29 (DHLA) 12 ] 3− composition, exhibiting absorption and photoluminescence spectra similar to those of Ag 29 (BDT) 12 (TPP) 4 NCs. 29 We have recently imparted optical activity to the NCs by using enantiomeric DHLAs and demonstrated mirror image CD and circular polarized luminescence (CPL) spectra.…”
Section: Introductionmentioning
confidence: 62%
“…The HR-TEM images of the Ag 29 (DHLA) 12 NCs showed that they are 2.44 nm in size and revealed no larger NPs nor any form of aggregation. [68] The nucleation and growth of these Ag 29 NCs were demonstrated by van der Linden and coworkers [71] through mass spectrometry and X-ray absorption spectroscopy (XAS) studies. Since the initial growth and nucleation involved the formation of larger NPs, a mass spectrometric analysis was not successful in capturing the details of the first half, which is a bottom-up process.…”
Section: Combination Of Both Bottom-up and Top-down (Cbbt) Methodsmentioning
confidence: 96%
“…In the second stage, during the top-down method, the evolution of Ag 29 NCs occurred via Ag 28 and Ag 26 NCs, as suggested by the mass spectrometry data (Figure 8C). The remarkable stability of Ag 29 NCs (8esystem, a close shell electronic structure) is the , [71] Copyright 2018 American Chemical Society major driving force for this two-step synthesis. Extended time-dependent information about coordination numbers generated from X-ray absorption fine structure (EXAFS) data (Figure 8D) shows the decrease in Ag-Ag and increase in Ag-S coordination number over time, supporting the two-step mechanism.…”
Section: Combination Of Both Bottom-up and Top-down (Cbbt) Methodsmentioning
confidence: 99%
“…93 Due to specific isotope patterns of the metals (Au, Ag, Pt, Pd, etc. ), HR-MS has proven particularly useful to determine the composition of alloyed nanoclusters, in particular for gold-doped silver [94][95][96][97][98] and silver-doped gold [99][100][101][102][103] nanoclusters. MS investigations of Pt and Pd doping on noble metal clusters were also reported.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%